Colombian Orchidaceae: A Catalogue of the Pleurothallidinae - Karremans, Adam P.; Moreno, Juan Sebastián; Gil-Amaya, Karen; Gutiérrez Morales, Nicolás; Espinosa, Felipe; Mesa, Santiago; Restrepo, Eugenio; Rincón-González, Milton; Serna, Alejandra; Sierra-Ariza, Mario; Vieira-Uribe, Sebastián (Lankesteriana: International Journal on Orchidology, 2023)
Colombia is a major biodiversity hotspot, having one of the richest orchid floras in the world. The country spans over a million square kilometers of land, hosting a multitude of different ecosystems thanks to the complexity of its mountainous systems and influences from neighboring countries in Central and South America, as well as the Atlantic and Pacific coastlines. Prior studies found an estimated 3591–4270 species of orchids occurring in Colombia, making it the most species-rich plant family in the country. About 35% of those orchids are members of the Pleurothallidinae subtribe, the largest group in the family and also that with the highest rate of species discovery. Here we record 1862 species of pleurothallids for the country, a significant increase from the 1286–1529 range estimated just a few years ago. We expect Pleurothallidinae to represent close to half the Colombian orchid flora. Colombia hosts roughly one third of all currently known taxa in the subtribe, and close to 60% of these species are found nowhere else in the world. These are clear indicators that the country is a highly important center of pleurothallid diversity and a key target for their conservation. The most species rich genera in the country are Stelis (521 species), Lepanthes (377 species), Pleurothallis (248 species) and Masdevallia (171 species). Country-level distribution is given for each accepted species. The closest floristic affinity is found with Ecuador, with which Colombia shares over 76% of the non-endemic Pleurothallidinae species, followed in the distance by Venezuela and Peru with just above one quarter of the non-endemics being shared. Numerous new country records are presented in the catalogue, many of which are illustrated with color photographs. We provide a full list of homotypic synonyms for each accepted taxon, as well as an annotated list of excluded taxa and newly proposed synonyms. Heterotypic synonyms are not listed, unless they are based on Colombian material. Typification for each accepted species is presented, with lectotypes, neotypes and epitypes being selected whenever necessary and available, as well as information regarding published illustrations.